Effect of the composition of activated carbon from coconut shell and paraffin on the performance of a carbon paste electrode for the detection of Pb(II) - Habibi, Haadi Farros (Journal of Experimental and Applied Physics, 2025)
This study examines the effects of the ratio on the composition of carbon paste electrodes with carbon derived from coconut shells and the feasibility of these electrodes as working electrodes in the cyclic voltammetry method for the measurement of lead Pb(II) values. In this study, measurements were conducted on a Pb(II) lead solution with a working electrode comprising a carbon paste electrode derived from coconut shell charcoal. The sensitivity,repeatability, and linearity of the electrode were evaluated in the measurement of lead Pb(II) by the cyclic voltammetry method. This study was conducted with the objective of identifying the optimal electrode composition for the measurement of lead Pb(II) by cyclic voltammetry. Three variations of electrode composition were prepared, 6:4, 7:3, and 8:2, to ascertain the impact of electrode composition on the sensitivity of the measurement. The feasibility of carbon paste electrodes as a working electrode in the cyclic voltammetry method was evaluated by conducting experiments with variations in the concentration of lead pb(II) solutions, 1 ppm, 2 ppm, 4 ppm, and 8 ppm. The test results demonstrate that the composition of the carbon paste electrode influences the measurement outcomes. The optimal composition is 8:2, which produces the highest peak values of (Ipa) and (Ipc) currents compared to other electrode compositions. Additionally, carbon paste electrodes comprising coconut shell charcoal materials exhibit good repeatability and linearity values, meeting the established standards. As a result, the electrode can be deemed suitable for use as a working electrode in the electrochemical analysis method.